Envolvimento do canal TRPA1 nos comportamentos do tipo depressivo e ansioso em um modelo de esclerose múltipla progressiva em camundongos - Péres, Diulle Spat (2020)
Background and Purpose: Progressive multiple sclerosis (PMS) is a neurological disease associated with the development of depression and anxiety, and treatments available are unsatisfactory. The transient potential receptor ankyrin 1 (TRPA1) is a cationic channel activated by oxidative compounds, and the blockage of this receptor can reduce depression and anxiety-like behaviors in naïve mice. Thus, we investigated the role of TRPA1 in depression and anxiety-like symptoms in a PMS model in mice. Experimental Approach: PMS model was induced in C57BL/6 female mice by the experimental autoimmune encephalomyelitis (EAE). Nine days after the PMS-EAE induction, the behavioral tests (tail suspension and elevated plus maze) were performed to verify the effects of sertraline (positive control), selective TRPA1 antagonist (A-967079) and antioxidants (α-lipoic acid and apocynin). Mice’s prefrontal cortex and hippocampus were collected to evaluate biochemical and inflammatory markers. Key Results: PMS-EAE induction did not induce locomotor changes but caused depression and anxiety-like behaviors, which were reversed by sertraline, A-967079, α-lipoic acid, or apocynin treatments. The neuroinflammatory markers (Aif1, Gfap, Il1b, Il17, and Tnfα) were increased in mice’s hippocampus. Moreover, this model did not alter TRPA1 mRNA expression levels in the hippocampus but decrease TRPA1 mRNA levels in the prefrontal cortex. Moreover, PMS-EAE induced an increase in NADPH oxidase and superoxide dismutase activities, as well as an increase in TRPA1 endogenous agonists levels, H2O2 and 4-HNE. Conclusion and Implications: TRPA1 plays a fundamental role in depression and anxiety-like behaviors as observed by the PMS-EAE model and shows a possible pharmacological target for treating these symptoms in patients affected by PMS.